Current and future therapeutic regimens for nonalcoholic fatty liver disease and nonalcoholic steatohepatitis. Issue 1 (5th July 2018) - Younossi, Zobair M.; Loomba, Rohit; Rinella, Mary E.; Bugianesi, Elisabetta; Marchesini, Giulio; Neuschwander‐Tetri, Brent A.; Serfaty, Lawrence; Negro, Francesco; Caldwell, Stephen H.; Ratziu, Vlad; Corey, Kathleen E.; Friedman, Scott L.; et al.
Abstract : Nonalcoholic fatty liver disease (NAFLD) and its progressive form non‐alcoholic steatohepatitis (NASH), are rapidly becoming among the top causes of cirrhosis, hepatocellular carcinoma, and indications for liver transplantation. Other than lifestyle modification through diet and exercise, there are currently no other approved treatments for NASH/NAFLD. Although weight loss can be effective, it is difficult to achieve and sustain. In contrast, bariatric surgery can improve metabolic conditions associated with NAFLD, and has been shown to improve liver histology. To have approved regimens for the treatment of NASH/NAFLD, several issues must be addressed. First, all stakeholders must agree on the most appropriate clinical trial endpoints for NASH. Currently, resolution of NASH (without worsening fibrosis) or reduction of fibrosis stage (without worsening NASH) are the accepted endpoints by the regulatory authorities. It is important to recognize the prognostic implication of histologic features of NASH. In this context, although histologic NASH has been associated with advanced fibrosis, it is not an independent predictor of long‐term mortality. In contrast, there are significant data to suggest that fibrosis stage is the only robust and independent predictor of liver‐related mortality. In addition to the primary endpoints, several important secondary endpoints, including noninvasive biomarkers, long‐term outcomes, and patient‐reported outcomes must be considered. In 2018, a few phase 3 clinical trials for the treatment of NASH have been initiated. Additionally, a number of phase 2a and 2b clinical trials targeting different pathogenic pathways in NASH are in the pipeline of emerging therapies. Conclusion : Over the next 5 years, some of these regimens are expected to provide potential new treatment options for patients with NASH/NAFLD. (Hepatology 2018;68:361‐371)